ANTIBACTERIAL ACTIVITY OF SEA GRAPES (Caulerpa racemosa) AGAINST Streptococcusmutans AND Shigella dysenteriae - Sri Hainil; Hesti Marliza; Maria Yunivista; Rastria Meilanda (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2023)
The Riau Islands are known as an island group in Indonesia that is famous for its wealth of marine plants. Among the prominent marine flora, sea grape (Caulerpa racemosa) is a marine plant that produces secondary metabolites including alkaloids, saponins, phenolics, and flavonoids which have been proven to have antibacterial properties. Previous research showed that 70% ethanol extract from sea grapes exhibited strong antibacterial activity. However, there is no detailed information regarding the ability of the n-hexane and ethyl acetate fractions of sea grapes as antibacterials. This study aims to examine the antibacterial effects of n-hexane and ethyl acetate fractions from sea grapes against Streptococcus mutans and Shigella dysenteriae. The sea grape extraction process is carried out through the maceration method using 95% ethanol solvent, followed by the fractionation stage using the liquid-liquid extraction method. This fractionation process involves the use of non-polar (n-hexane) and semi-polar (ethyl acetate) solvents. The test method used was disk paper diffusion with varying fraction concentrations: 500 μg/disc, 400 μg/disk, 300 μg/disc, and 200 μg/disk. The positive control for this study used 30 μg/disc of tetracycline, because tetracycline is known as a broad-spectrum antibiotic. Meanwhile, the negative control used 10% DMSO. Findings from the research stated that the n-hexane fraction could not stop the growth of Streptococcus mutans bacteria, while the ethyl acetate fraction was able to inhibit the development of these bacteria. The average diameter at a concentration of 500 μg/disk was 9.2 mm, 400 μg/disk is 8 mm, 300 μg/disc is 7.7 mm, and 200 μg/disc is 6.5 mm. However, neither the ethyl acetate nor n-hexane fractions showed an inhibition zone against Shigella dysenteriae bacteria